Cultural cooperation between Russia and Japan - Magdeev, Rafik. R. (2021)
It is necessary to conduct an analysis of relations between Japan and Russia to determine the main trends and prospects for joint development. The purpose of the article is to study and disclose the stages of development of cultural relations between Russia and Japan and determine its features, highlight the most pressing problems of relations and identify possible ways to build strong interstate relations. The methodological basis of the study is the analytical method, for a comprehensive analysis of the changes that occurred during the development of cultural relations between Japan and Russia. Also a prerequisite is compliance with the principles of historicism and objectivity. In the course of studying used the method of study and systematization of literature. As a result of studying the problem, we can evaluate the historical development of cultural relations between Russia and Japan. Assess the state of relations between Russia and Japan and uncover limitations and growth points to strengthen relations between Japan and Russia. The results of this study can be useful as Japanologists and to specialists dealing with the problems of Asia-Pacific as a whole.